The Impact of Covid 19 Lockdowns on Remittance Dependent Households: The Case of Makokoba, Bulawayo - Machikicho, Susan; Magura, Juana; Magura, Tennyson T. S. (Advances in Social Sciences Research Journal, 2022)
Remittances continue to be an integral part of livelihood strategies that have been used for a long time particularly in low-income nations. They remain critical for the survival of recipients at household level. The study seeks to unravel the adverse effects on sustenance and survival of households in Makokoba that has been caused by the novel corona or Covid-19. The research methodology underpinning the study is qualitative with interviews and questionnaires being used to collect data to establish the impact of low remittances on receivers from the diaspora family. The study found out that the majority of households rely on remittances from the diaspora families for sustenance and that due to the Corona Virus, loss of jobs has had negative impacts on the senders hence their inability to remit back home. The study furthermore, noted that remittance dependent households in Makokoba have been left vulnerable as they struggle to meet their basic daily needs. The study also revealed that they have turned to unsustainable income that can hardly sustain them. However, the study recommends the need for the government and its stakeholders to come up with alternative measures to reduce over-reliance on remittance inflows.